Towards fairer conservation: Perspectives and ideas from early‐career researchers - Lucy J. Archer; Helen S. Müller; Lizzie P. Jones; Heidi Ma; Rosalind A. Gleave; Aline da Silva Cerqueira; Thalassa McMurdo Hamilton; Yara Shennan‐Farpón (People and Nature, 2022)
Abstract The Black Lives Matter Movement, which gained unprecedented global momentum in mid‐2020, triggered critical reflection on systemic discrimination of disadvantaged groups across many domains of society. It prompted us, as early‐career researchers (ECRs) in conservation science, to examine our own awareness of ongoing injustices within our field, the role we play in perpetuating or countering these injustices, and how to move forward. Colonialist ideologies and power dynamics throughout the history of conservation practice and research have left a long‐lasting legacy of inequality and systemic racism. While improvements have been made, these legacies continue to influence teaching and practice today. In this perspective piece, we reflect on the impacts of conservation’s colonial past and how the sector has developed. We then explore how current traditional routes into conservation, and the dominance of these approaches, can leave ECRs underprepared to address modern‐day conservation issues due to a limited understanding of conservation’s history and key theories from other fields. We end by offering a set of suggestions encouraging others to learn and practise fairer and more inclusive conservation practices. Read the free Plain Language Summary for this article on the Journal blog.